SEGMENTASI KARAKTERISTIK DEBITUR MENGGUNAKAN ALGORITMA X-MEANS - , NURLITA KUSUMA DEWI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The event of debtor is failed to pay or arrears of payment is called default. One of the way to minimize default is we can recognize debtor characteristic who usually gets default experience using x-means algorithm. Clustering using x- means algorithm is a development from k-means cluster. X-means forms an initial cluster using k-means. Each formed initial cluster is divided into two clusters based on BIC criteria. This process is repeated until there is no cluster which can not be divided. X-means needs less computation than k-means and is capable to optimize the number of clusters formed.